The Effectiveness of the Pre-Reading Plan (PREP) Strategy in Enhancing Reading Comprehension: A Case Study of Eighth Grade Students at SMPN 3 Panca Rijang - Arnas, Riska; Wahyuddin, Nur Rahmah; Hermansyah, Sam; M. Daming, Hamdi (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study examines the effectiveness of the Pre-Reading Plan (PREP) strategy in enhancing reading comprehension among eighth-grade students at SMPN 3 Panca Rijang. Employing a pre-experimental design with a one-group pretest-posttest method, the research involved 20 students and one English teacher as participants. Data collection included pretests, posttests, and questionnaires, analyzed through qualitative and quantitative methods. Results indicated significant improvements in students' reading comprehension post-implementation of the PREP strategy, with the percentage of students meeting the minimum completeness criteria increasing from 35% to 70%. Additionally, students exhibited higher engagement levels during learning activities, and the teacher's performance in classroom management improved. Many students expressed a positive interest in the PREP strategy. These findings support the conclusion that the PREP strategy effectively enhances reading comprehension among students. It is recommended that the PREP strategy be adopted more widely to foster improved reading skills in English language learning contexts, as it encourages students to activate prior knowledge and engage more deeply with the reading material. Overall, this research highlights the importance of interactive and student-centered teaching strategies in improving reading comprehension and fostering a positive learning environment.